Hubungan Lama Pemberian Asi Eksklusif Dengan Awal Menstruasi Post Partum Tanpa Kontrasepsi Tambahan - Firza Fatchya; Tri Budi Wiryanto; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: This research aimed to analyze the relationship between duration of exclusive breastfeeding with the early postpartum period without additional contraception. Methods: This analytic study was observational using cross sectional approach. This research was held in May 2013 at Sibela health center Surakarta. A sample of 60 study subjects was selected by exhaustive sampling. The inclusion criterias were mothers exclusively breastfeeding. Samples can not be selected if (1) mothers using contraception until the first post partum period. Biographical data sheet and fill the sample informed consent as a sign of approval. The data was collected by interview using a set of questionnaire. The data was analyzed using multiple linear regression models on SPSS 16.0 for Windows program. Results : From the analysis of the association this research shows a positive and significant relationship between duration of exclusive breastfeeding with early post partum period. Each increment 1 week long exclusive breastfeeding will extend the return of the early post partum period for 0.69 weeks (b = 0.69; CI95% = 0:47 to 0.90, P = <0.001). Analysis of the relationship this variable has controlling the influence of confounding variables (age, BMI, additional food). Conclusion:. There is a relationship between duration of exclusive breastfeeding with the early post partum period without additional contraception. Increasingly duration of exclusive breastfeeding will extend the return of the early post partum period. Key words : exclusive breastfeeding, early post partum period